Halogen bonding: an electrostatically-driven highly directional noncovalent interaction - Politzer, Peter; Murray, Jane S.; Clark, Timothy (Physical Chemistry Chemical Physics, 2010)
A halogen bond is a highly directional, electrostatically-driven noncovalent interaction between a region of positive electrostatic potential on the outer side of the halogen X in a molecule R-X and a negative site B, such as a lone pair of a Lewis base or the pi-electrons of an unsaturated system. The positive region on X corresponds to the electronically-depleted outer lobe of the half-filled p-type orbital of X that is involved in forming the covalent bond to R. This depletion is labeled a sigma-hole. The resulting positive electrostatic potential is along the extension of the R-X bond, which accounts for the directionality of halogen bonding. Positive sigma-holes can also be found on covalently-bonded Group IV-VI atoms, which can similarly interact electrostatically with negative sites. Since positive sigma-holes often exist in conjunction with negative potentials on other portions of the atom's surface, such atoms can interact electrostatically with both nucleophiles and electrophiles, as has been observed in surveys of crystallographic structures. Experimental as well as computational studies indicate that halogen and other sigma-hole interactions can be competitive with hydrogen bonding, which itself can be viewed as a subset of sigma-hole bonding.